Covert observation to find if patient hospital clothing saves radiotherapy treatment room time, and the issue of a questionnaire to find if this is detrimental to patients' experience of radiotherapy. Issue 4 (22nd April 2013) - Farnan, M.; Blyth, C.
Abstract: Background: Radiotherapy departments are having to work more efficiently to cope with increasing demand for radiotherapy resources. Radiotherapy treatment room efficiency may be increased by the introduction of hospital clothing as this negates the need for patient changing in the treatment room. However, studies have shown that hospital clothing can have a negative effect on patient dignity. It is therefore important to balance potential time saving with any detriment to patients. Purpose: This study examined the effect that hospital clothing had on the time patients spend in the treatment room and aimed to identify patients' opinions of the clothing. Materials and methods: Potential time saving was determined by covertly timing patients currently undergoing radiotherapy treatment as they entered and exited the treatment room. A total of 348 patients were timed in their own clothing and 341 were timed when they wore hospital clothing. The timings of these two groups were compared to determine whether hospital clothing saved treatment unit time. Patient opinions of the clothing were examined by issuing a short questionnaire, designed to gather ordinal data, at the end of their course of treatment. Questionnaires were issued only to patients who had worn hospital clothing in the radiotherapy department. Results: Introducing hospital clothing saved a significant amount of treatment room time and patients were generally positive about wearing the clothing. Conclusion: It is suggested that hospital clothing is a welcome addition to the radiotherapy department to increase efficiency without detriment to patients.